THE ROLE OF BUSINESS LAW IN DIGITAL MARKETING IN INDONESIA - Fazry, Muhammad (PROCURATIO: Jurnal Manajemen & Bisnis, 2023)
This study explores the crucial role of business law in the context of digital marketing in Indonesia. The research focuses on analyzing the legal framework that governs various aspects of digital marketing, including consumer protection, online transactions, intellectual property rights, and contractual agreements. By examining the implementation and effectiveness of business law in the digital marketing landscape, this study aims to provide insights into how legal regulations facilitate fair and secure digital business practices. Business law plays a central role in regulating and shaping digital marketing in Indonesia. By providing a strong legal framework, business law helps create a business environment that is fair, integrity, and innovative. In an era where the Internet and technology dominate, the existence of business law is essential to ensure sustainable economic growth and the well-being of all parties involved in the digital business ecosystem. The findings offer valuable implications for policymakers, businesses, and consumers in optimizing the digital marketing environment and ensuring compliance with relevant legal requirements.